THE EFFECT OF INTERIOR DESIGN ON EMPLOYEE’S JOB SATISFACTION - Shareef, Vian A; Husien, Husein A; Omer, Soran Kakarash (Journal of process management and new technologies, 2018)
Abstract This study investigates the impact of interior design on employee’s job satisfaction, and it is an exploratory study about employee’s opinion to their office interior design at the presidency offices of both Koya and Ishik universities. As well as interior design is as an independent variable and job satisfaction is as dependent variable. A questionnaire is used and its involving of thirty one phrases. Also, the scope of the population exists the employees of Koya and Ishik university, which are selected randomly and have been returned and analyzed, the following appropriate. Furthermore, statistical methods are used to analyze data and to test research hypotheses such as, regression, model summary statistics, one-sample t-test, mean and standard deviation, in addition (ANOVA) using statistical software program (SPSS.v.20).The main result of the study is summarize the result that interior design has an effect on job satisfaction of employees specify the result in both universities.